Digital Activism as a New Arena of Human Rights Advocacy in Muslim Society: The #MeToo Movement in Egypt - Novi Rizka Amalia; Ramadina, Annisa (Jisiera: The Journal of Islamic Studies and International Relations, 2026)
The expansion of digital technology has significantly transformed the landscape of human rights advocacy, particularly in socio-political contexts where public discourse is constrained. This study examines how digital activism constitutes a new arena of human rights advocacy within Muslim society, with a specific focus on the #MeToo movement in Egypt. While discussions on sexual violence in Egypt have historically been limited by patriarchal norms, cultural stigma, and political restrictions, digital platforms have enabled survivors to articulate their experiences and challenge dominant social narratives. Using a qualitative case study approach and the Transnational Advocacy Network (TAN) framework, this research analyses how digital activists employ strategies such as information politics, symbolic politics, leverage politics, and accountability politics in advancing gender-related human rights claims. The findings reveal that digital activism not only amplifies marginalized voices but also reconfigures the space of advocacy by transforming private experiences into collective public discourse. Importantly, the study demonstrates that digital activism in Egypt operates within a Muslim socio-religious context, where advocacy efforts are shaped by Islamic ethical principles. Activists strategically integrate values such as justice (adl), human dignity (karamah), and the protection of honor (hifz al-‘ird) to legitimize their claims and enhance social acceptance. This process reflects what the study conceptualizes as Islamic ethical adaptation, where global human rights norms are localized within religious framework.